PENGELOLAAN ADMINISTRASI DAN SUPERVISI DI PERGURUAN TINGGI DALAM MENINGKATKAN MUTU PENDIDIKAN - Angga Pratama; Desy Eka Citra Dewi (STKIP Subang, 2023)
ABSTRACT Higher education as an educational institution must be able to provide services that can maximize the satisfaction of its user community, which in turn can encourage the development of higher education. One of the strategies implemented by private universities to maintain and increase the number of students is to provide quality services. It is expected to be able to meet student expectations with optimal service. Likewise, public universities must do the same. However, in reality, the administration and supervision system in several universities has been carried out but is not running optimally, causing problems that result in the quality and quality of education in a university. This study aims to find out what the quality of Academic Administration services and supervision system at UINFAS Bengkulu is like in improving the quality of education. The approach used by researchers is a qualitative approach that uses a narrative format to interpret data and facts in the field. The results found indicate that the quality of service of the Academic Administration and supervision system at UINFAS Bengkulu is ranked in the Good category in all aspects. Keywords: Administration, supervision, higher education